(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Chikungunya is one of the most rapidly spreading Aedes mosquito-borne viral infectious diseases. Recently in Bangladesh it has emerged as an important public health issue. Chikungunya virus (CHIKV) mostly spread by Aedes aegypti and Aedes albopictus, an anthropophilic mosquito species widely distributed in Asia, Europe, Africa and America. Our objective was to determine the clinical, biochemical and radiological features of patients at the acute phase of CHIKV infection. The purpose of study was to evaluate the literature and summarize the current state of CHIKV-associated disease, including clinical presentation, diagnosis, risk factors for development of severe diseases, complications and treatment. We present 253 confirmed cases of chikungunya having different clinical presentations occurring among adult patients from different background including foreigner in Dhaka city, admitted in a tertiary level hospital situated in Gulshan from march’17 to November 2017 . All patients had fever and joint pain. Other common features were rash, diarrhoea, vomiting, confusion, and altered liver biochemistry. Adult patients with multiple co-morbidities admitted in hospital with male preponderance of 59 % and rest were female 41%. Most common complication was post CHIKV arthritis (79%) and rest of the less common complications were post viral asthenia (34%), myocarditis (27%), pneumonitis (30%). Dengue was excluded in all patients. Paracetamol remained the mainstay of treatment during febrile periods, but around 62% of the patients had prolonged joint symptoms requiring non-steroidal antiinflammatory drugs, colchicines, steroid. Among joint involvement, ankle joints were commonly involved joint presented with post viral arthritis. Since there is no specific treatment of chikungunya, prevention through vector control and public health education is the key. J Bangladesh Coll Phys Surg 2019; 37(3): 124-129